2015
DOI: 10.12693/aphyspola.127.791
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions and Fundamental Ferroelectric Dispersion in DMAAl1-xCrxS Crystals

Abstract: This paper presents the results of investigations of the temperature dependence of heat capacity and dielectric dispersion in the vicinity of ferroelectric-ferroelastic phase transition of dimethylammonium metal sulphate hexahydrate crystals DMAAl1−xCrxS. In particular, it is shown that the isomorphous substitution of metal ion noticeably changes the temperature of phase transition and parameters of the fundamental ferroelectric dispersion observed around Tc1. These changes are explained in terms of clusters s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…A DC electric eld of 7.9 kV/m applied during cooling reveals peaks in the pyroelectric currents for both samples and demonstrates Cr dependent T c evolution. e temperature dependences of the dielectric properties for both investigated crystals fairly well correlate with the data of previous investigations 37 and obey the Curie-Weiss law both in the paraelectric (+) and ferroelectric (−) phases in the vicinity of the ferroelectric phase transition. Together with the data of DSC study 37 this clearly con rms a second order of the phase transition.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A DC electric eld of 7.9 kV/m applied during cooling reveals peaks in the pyroelectric currents for both samples and demonstrates Cr dependent T c evolution. e temperature dependences of the dielectric properties for both investigated crystals fairly well correlate with the data of previous investigations 37 and obey the Curie-Weiss law both in the paraelectric (+) and ferroelectric (−) phases in the vicinity of the ferroelectric phase transition. Together with the data of DSC study 37 this clearly con rms a second order of the phase transition.…”
Section: Resultssupporting
confidence: 87%
“…e phase transition is of the order-disorder type with a symmetry change 2/m → m. It is connected with ordering of the polar DMA cations which execute hindered rotations around their C-C direction in the paraelectric phase and order only in the spatio-temporal average in the ferroelectric phase 35 . Metal ion isomorphous substitution in the above mentioned family of compounds can be an additional degree of freedom in the composition-property engineering 36,37 . Here we report that the incorporated magnetic Cr cations can participate in ME interactions in the [NH 2 (CH 3 ) 2 ]Al 1−x Cr x (SO 4 ) 2 × 6H 2 O crystals with ability to tune magneto-electric functionality.…”
mentioning
confidence: 99%
“…Previous studies showed that substitution of aluminium with chromium in the isomorphic analogue DMAAlS crystals noticeably affects the phase transition temperature [6,7]. Moreover, paper [8] reported a successful creation of the paramagnetic order in the initially diamagnetic DMAAlS crystal by such an isomorphous substitution of a metal ion.…”
Section: Introductionmentioning
confidence: 95%
“…Curie-Weiss law parameters for DMAGaS and DMAAlS doped with chromium in different concentration (the data marked with * are taken from[7]). …”
mentioning
confidence: 99%
“…Taking into account that the ferroelectric ordering is realized in the numerous organic-inorganic ferroics [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], the substitution of the metal ion in the inorganic anionic complexes would give the possibility to introduce the magnetic ordering into a previously diamagnetic matrix. In such a way using, for example, the partial metal ion substitution one can generate the magnetoelectric effect in the known ferroelectric material.…”
Section: Introductionmentioning
confidence: 99%